TAKING DISABILITY SERIOUSLY ON THE FEMINIST DISABILITY STUDIES CRITIC TO THE MAINSTREAM FEMINISM - Bernardini, Maria Giulia (Gênero & Direito, 2015)
The discipline of Feminist Disability Studies (FDS) emerges in the mid-Eighties as a critique of both Feminist and Disability Studies, considered “guilty” of excluding women with disabilities from their theorization and, therefore, incapable to represent them as subjects. After a brief analysis of the similarities and the differences between the conditions of oppression experienced by people with disabilities and women, in this paper I first analyse some of the reasons that may be present behind the silence of Feminism on disability, then I show the importance of FDS for the feminist inquiry. Finally, I conclude by focusing on a recent and interesting point of convergence between Feminism and FDS, namely, the theme of vulnerability and dependency